Reimagining child soldiers in international law and policy - Drumbl, Mark A. (Oxford : Oxford University Press, 2012)
Child soldiers are generally perceived as faultless, passive victims. This ignores that the roles of child soldiers vary from innocent abductee to wilful perpetrator. This book argues that child soldiers should be judged on their actions and that treating them like a homogenous group prevents them from taking responsibility for their acts.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Child soldiers -- Legal status, laws, etc